L‐type Ca2+ channel current characteristics are preserved in rat tail artery myocytes after one‐day storage. (23rd April 2014) - Mugnai, P.; Durante, M.; Sgaragli, G.; Saponara, S.; Paliuri, G.; Bova, S.; Fusi, F.
Abstract Aim To develop a cheap and simple method of storing for 24‐h vascular tissue and single myocytes while preserving therein the biophysical and pharmacological characteristics of L‐type Ca2+ channels and contractile activity. Methods Rings or vascular smooth muscle cells obtained from the rat tail main artery were used either freshly (R0h and VSMC0h) or stored for 24 h (R24h and VSMC24h) at 4 °C, to record whole‐cell L‐type Ca2+ currents (ICa(L)) or measure contractile responses. Results R0h/VSMC0h and R24h/VSMC24h comparably contracted when stimulated with phenylephrine, high KCl or ATP. In both VSMC0h and VSMC24h, ICa(L) was identified and characterized as a stable inward current for at least 35 min; ICa(L) was comparably inhibited by the Ca2+ antagonists nifedipine, verapamil and diltiazem and increased by the Ca2+ channel agonist (S)‐(‐)‐Bay K 8644; current density and current–voltage relationships were similar; at more hyperpolarized holding potentials, ICa(L) intensity increased comparably; nifedipine shifted the steady‐state inactivation curve towards more negative potentials, while verapamil blocked ICa(L) in a frequency‐dependent manner and slowed down the rate of recovery from inactivation in a comparable way. Conclusion Findings show that smooth muscle contractile activity and the biophysical and pharmacological features of L‐type Ca2+ channels are similar in VSMC24h and VSMC0h. The fact that reproducible results were obtained in vascular myocytes up to 24 h after dissociation may facilitate vascular smooth muscle cell investigation by increasing throughput and reducing the number of animals required.